Knowledge and effects of menstrual distress among PCL nursing students of Pokhara, Nepal - Khadka, Asmita; Shrestha, Ishwori Byanju; Pahari, Sandip (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Menstrual distress includes a range of physical, psychological, and emotional symptoms that can negatively affect students’ academic performance, social life, and well-being. Nursing students may face added challenges due to academic pressures and clinical responsibilities. This study aimed to assess the knowledge and effects of menstrual distress among PCL nursing students in Pokhara, Nepal. Methods: A quantitative, cross-sectional study was conducted among 303 PCL nursing students using a census method. Data were collected through a modified Menstrual Distress Questionnaire (MEDI-Q), developed based on the standard MEDI-Q. Permission to use and adapt the MEDI-Q was obtained from the original author. Data were entered in EpiData, and analyzed using IBM SPSS v.22. Chi-square was used, with p < 0.05 considered statistically significant. Results: Results showed that majority of the students (91.74%) were aware of menstrual discomfort, most of them (83.82%) had knowledge of gastrointestinal issues, nearly all (98.34%) understood cognitive changes, and majority (94.71%) recognized physiological changes. Menstrual and inter-menstrual phases showed higher levels of reported distress. Study year and pain intensity were significant predictors of menstrual distress, whereas factors like age, religion, and ethnicity were not. Conclusion: Despite high awareness, menstrual distress is often normalized and unaddressed, affecting students’ mental health, academic performance, and clinical competence. The findings highlight the need for targeted interventions such as institutional support and access to menstrual health resources to improve the well-being and academic experiences of nursing students.